To-be-cut piece of laminated chip inductor, preparation method of to-be-cut piece and single sintered body

By adding a starch layer to the to-cut part of the laminated chip inductor, the problems of local depression, deformation and adhesion during the cutting process are solved, and the effects of high appearance pass rate, low adhesion rate and good sintering density are achieved.

CN119446702APending Publication Date: 2025-02-14CHAOZHOU THREE CIRCLE GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661387.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing laminated chip inductors are prone to local depressions, deformation and adhesion during the cutting process, which affects the appearance and reliability of the product.

Method used

A starch layer is added between the green layer and the PET layer. The starch layer consists of an upper layer and a lower layer. The upper layer is in contact with the green layer and the lower layer is in contact with the PET layer. The starch layer provides buffering during the cutting process, avoids adhesion and gradually decomposes during the sintering process.

Benefits of technology

The appearance pass rate of the cut single green body is improved, the adhesion rate is reduced, and the density and performance of the sintered body is ensured without changing the green body formula.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446702A_ABST
    Figure CN119446702A_ABST
Patent Text Reader

Abstract

The invention provides a to-be-cut piece of a laminated chip inductor, a preparation method of the to-be-cut piece and a single sintered body, and belongs to the technical field of laminated chip inductors. A to-be-cut piece of the laminated chip inductor sequentially comprises a PET layer, a starch layer and a green body layer from bottom to top, the starch layer comprises an upper layer and a lower layer, the lower layer is in contact with the PET layer, and the upper layer is in contact with the green body layer; the starch layer comprises starch, a binder and an organic solvent, the mass of the starch in the upper layer is larger than that of the starch in the lower layer, and the mass of the binder in the upper layer is smaller than that of the binder in the lower layer by taking the mass of the starch layer as a whole. According to the invention, the starch layer is added in the green body layer and the PET layer, so that the to-be-cut piece does not generate an adhesion phenomenon after being cut and sintered, the appearance and separability of a single green body are good, the appearance qualification rate of the single green body is increased, the adhesion rate of the single green body and the sintering adhesion rate are reduced, and the sintering density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laminated chip inductors, and in particular to a laminated chip inductor to-be-cut piece and a preparation method thereof, and a single sintered body. Background Art

[0002] As one of the most commonly used ceramic multilayer electronic components in electronic products and modern equipment, multilayer chip inductors are designed to achieve low loss, high inductance and strong reliability while being further miniaturized to meet the requirements of the gradual miniaturization and lightweight of intelligent equipment.

[0003] The preparation process of conventional multilayer chip inductors includes pulping, casting, punching, printing, lamination, pressing, cutting, sintering and external electrode preparation. The green blanks obtained after the lamination process and pressing need to be placed on a cutting substrate for precise cutting to obtain single inductor products with qualified appearance and good separation. However, in the actual cutting process, the extrusion of the green blanks by the cutting knife or the insufficient pressing strength of the green blanks often cause appearance defects such as rough cutting bottoms or unevenness due to the lack of buffering, local depressions or deformation caused by collisions. In addition, the miniaturized products still have partial adhesion and are difficult to completely separate after being cut into single pieces due to the presence of adhesive components in their green blanks. In the subsequent sintering process, they are further sintered and adhered at high temperatures, which seriously affects the qualification rate and reliability of the inductor products. To address the above problems, the prior art adopts changing the binder formula in the green body or sprinkling starch particles on it after cutting to prevent sticking. However, changing the formula is cumbersome, time-consuming and has great limitations. It is difficult to accurately control the dosage of dispersed starch particles. In addition, excessive dust or large particle size can easily pollute the environment and affect the subsequent sintering process. Excessive large starch particles are difficult to remove and may even enter the interior of the green body during high-temperature sintering, resulting in reduced density and other quality accuracy problems in the sintered ceramic parts. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a piece to be cut of a laminated chip inductor and a preparation method thereof, as well as a single sintered body.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, a piece to be cut of a laminated chip inductor is provided, which comprises, from bottom to top, a PET layer, a starch layer and a green layer, wherein the starch layer comprises an upper layer and a lower layer, the lower layer is in contact with the PET layer, and the upper layer is in contact with the green layer;

[0007] The components of the starch layer include starch, a binder and an organic solvent, wherein, based on the mass of the starch layer as a whole, the mass of the starch in the upper layer is greater than the mass of the starch in the lower layer, and the mass of the binder in the upper layer is less than the mass of the binder in the lower layer.

[0008] The present invention adds a starch layer between the green sheet layer and the PET layer. The starch layer can increase the buffering effect of the cutting knife during the cutting and separation process. On the basis of maintaining the required cutting accuracy, the green sheet layer that originally absorbs the residual stress of the cutting knife is replaced with the starch layer, so as to avoid the appearance defects such as local depression and deformation of the single green sheet after cutting. Moreover, a single green sheet with a starch layer evenly distributed on the bottom of the green sheet is obtained after cutting, which can prevent direct contact between products and will not cause adhesion when used for the preparation of small products. In addition, during the sintering and heating process of a single green body, even if the glass component in the green body softens and becomes a viscous substance, the existence of the starch layer can alleviate the sintering adhesion phenomenon, and the substances in the starch layer can begin to decompose in the debinding stage (starch decomposition temperature is 300-400℃, and complete decomposition temperature is 550℃). Compared with the traditional powder sprinkling anti-sticking method, on the one hand, the uniformity of starch distribution is improved, the material utilization rate is higher and the anti-sticking effect is better. On the other hand, the starch layer on the outside of the green body gradually decomposes completely as the temperature rises, and will not enter the internal structure of the green body to affect the product quality or performance. A single sintered body with good density can still be obtained.

[0009] If the mass of starch in the upper layer of the starch layer is greater than that in the lower layer, the upper layer is in contact with the green body, and the contact surface density required for cutting is higher, and the hardness is correspondingly larger. Compared with the low starch mass in the lower layer, it is not easy to be pressed and deformed, and defects such as roughness at the cutting bottom can be minimized. On the contrary, if the mass of starch in the upper layer is less than that of the lower layer, the required cutting density and hardness requirements cannot be met, and the above effects cannot be achieved.

[0010] If the mass of the binder in the upper layer of the starch layer is less than that in the lower layer, the relatively higher binder component in the lower layer can enhance the bonding force between the lower layer and the PET layer, ensuring that the single green billet after cutting does not fall off during subsequent inspection and transportation. On the contrary, if the mass of the binder in the upper layer is greater than that in the lower layer, the mass of the starch in the upper layer is less than that in the lower layer. At this time, the bonding force between the upper layer and the green billet is too large, affecting the subsequent separation process, and the cutting density and hardness cannot be met.

[0011] In some embodiments, the polarity of the organic solvent in the upper layer is greater than the polarity of the organic solvent in the lower layer.

[0012] The polarity of the organic solvent in the upper layer is greater than that of the organic solvent in the lower layer. On the one hand, it can reduce the dissolution and erosion of the upper layer on the lower layer during the casting process. On the other hand, the difference in polarity of the organic solvent in the upper and lower layers of the starch layer is beneficial to control the diffusion rate and volatilization rate of the organic solvent in the upper and lower layers, further improving the bonding between the upper and lower layers of the starch layer and avoiding stratification during the cutting process.

[0013] In some embodiments, the organic solvent in the upper layer is at least one of ethanol, ethyl acetate, propyl acetate, toluene, and butanone; the organic solvent in the lower layer is at least one of toluene, xylene, propanol, isobutanol, and n-butanol.

[0014] Preferably, the organic solvent in the upper layer is at least two of ethanol, ethyl acetate, propyl acetate, toluene and butanone; the organic solvent in the lower layer is at least two of toluene, xylene, propanol, isobutanol and n-butanol.

[0015] More preferably, the organic solvent in the upper layer is one of a mixed solvent of ethanol and ethyl acetate, a mixed solvent of ethyl acetate and toluene, and a mixed solvent of ethyl acetate and butanone; the organic solvent in the lower layer is one of a mixed solvent of toluene and ethanol, a mixed solvent of toluene and isobutanol, a mixed solvent of toluene and n-butanol, and a mixed solvent of xylene and ethanol.

[0016] In some embodiments, based on 100 parts by mass of the lower layer slurry for preparing the lower layer, the lower layer slurry includes the following components in parts by mass: 20-45 parts of starch, 5-12 parts of binder, 49-64 parts of organic solvent, and the balance of plasticizer.

[0017] In some embodiments, based on 100 parts by mass of the upper layer slurry for preparing the upper layer, the upper layer slurry includes the following components in parts by mass: 25-55 parts of starch, 4-7 parts of binder, 38-67 parts of organic solvent, and the balance of plasticizer.

[0018] For example, in different embodiments, based on 100 parts by mass of the lower layer slurry for preparing the lower layer, the mass parts of the starch may be, but are not limited to, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 43 parts, and 45 parts;

[0019] The mass parts of the binder can be, but are not limited to, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, and 12 parts;

[0020] The mass parts of the organic solvent may be, but are not limited to, 49 parts, 51 parts, 53 parts, 55 parts, 57 parts, 59 parts, 62 parts, and 64 parts.

[0021] For example, in different embodiments, based on 100 parts by mass of the upper slurry for preparing the upper layer, the mass parts of the starch may be, but are not limited to, 25 parts, 27 parts, 29 parts, 31 parts, 33 parts, 35 parts, 37 parts, 39 parts, 41 parts, 43 parts, 45 parts, 47 parts, 49 parts, 51 parts, 53 parts, and 55 parts;

[0022] The mass parts of the binder may be, but are not limited to, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, and 7 parts;

[0023] The mass parts of the organic solvent can be, but are not limited to, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 49 parts, 51 parts, 53 parts, 55 parts, 57 parts, 59 parts, 62 parts, 64 parts, and 67 parts.

[0024] If the mass percentage of starch in the upper layer is too high, the viscosity of the slurry in the upper layer will be too high, the fluidity will be low, and the stacking density will be reduced, which will make the casting drying difficult. The quality of the upper layer in the obtained starch layer will be poor, which will affect the appearance quality of the single green billet after cutting and cause the single green billet after cutting to stick together. If the mass percentage of starch in the lower layer is too small, the viscosity of the slurry in the lower layer will be low, making it difficult to form the structure of the overall starch layer, and the starch layer will not play a buffering and anti-adhesion role.

[0025] If the mass fraction of the binder in the lower layer is too small, the flexibility of the obtained lower layer deteriorates and it is easy to crack during processing, and the hot pressing property is low, making it difficult to combine the PET layer and the lower layer.

[0026] The starch layer of the present invention comprises an upper layer and a lower layer, and adopts starch layer structures with different compositions. On the one hand, the viscosity of the contact surface between the starch layer and the green layer, that is, the viscosity of the upper layer of the starch layer, can be adjusted, and adverse conditions caused by too low or too high viscosity will not occur, such as the situation that the starch layer and the green layer are too tightly combined due to too high viscosity, resulting in poor adhesion, or the viscosity of the starch layer is too low to fix the green layer, resulting in partial detachment of the piece to be cut during the cutting process, and other adverse conditions; on the other hand, the starch layer structures with different compositions can be better removed during the sintering process, and will not affect the performance of the single green layer itself or the sintering process.

[0027] In some embodiments, the starch is at least one of corn starch, potato starch, and sweet potato starch.

[0028] In some embodiments, the binder is at least one of polyvinyl butyral, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, acrylic resin, and hydroxyethyl cellulose.

[0029] In some embodiments, the plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, di(di-ethylhexyl) adipate, di(di-ethylhexyl) sebacate, tricresyl phosphate, epoxidized soybean oil, and tributyl citrate.

[0030] In some embodiments, the thickness of the starch layer is 30-100 μm, for example, it can be but not limited to 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm; the thickness ratio of the upper layer and the lower layer is 0.6-1, for example, it can be but not limited to 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0.

[0031] If the thickness of the starch layer is too thick, it will increase the difficulty of cutting the piece to be cut, resulting in a waste of energy and materials, and it is not suitable for cutting green sheets with a small number of layers, and the applicability range of the green sheet layer thickness is small; if the thickness of the starch layer is too thin, the buffering effect of the starch layer is small and cannot play a compensatory role, resulting in the appearance defects of the single green sheet after cutting, such as rough and uneven bottom, local depression or deformation caused by collision, etc., which improves the appearance qualification rate of the single green sheet and reduces the adhesion rate.

[0032] If the thickness ratio of the upper layer to the lower layer is too large or too small, the bonding between the upper layer and the lower layer in the starch layer will be reduced, which is not conducive to use as a whole.

[0033] Preferably, the thickness of the starch layer is 40-80 μm, and the thickness ratio of the upper layer to the lower layer is 0.7-0.9.

[0034] When the thickness of the starch layer and the thickness ratio of the upper layer to the lower layer are within the above preferred ranges, the appearance qualification rate of a single green body is higher and the adhesion rate is lower.

[0035] In some embodiments, the thickness ratio of the green layer to the starch layer is 3.5-15, for example, but not limited to 3.5, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15.

[0036] In a second aspect, a method for preparing a piece to be cut of the multilayer chip inductor is provided, comprising the following steps:

[0037] Preparing an upper slurry and a lower slurry of the starch layer;

[0038] Casting the lower layer slurry on the PET layer to obtain the lower layer, and further casting the upper layer slurry on the lower layer to obtain the upper layer, thereby obtaining the starch layer;

[0039] The green sheet layer is placed on the starch layer to obtain pieces to be cut of the laminated chip inductor.

[0040] In a third aspect, a single sintered body of a multilayer chip inductor is provided. The piece to be cut of the multilayer chip inductor is placed on a substrate and cut, heated, debonded and sintered in sequence to obtain the single sintered body of the multilayer chip inductor.

[0041] Specifically, the method for preparing a single sintered body of the multilayer chip inductor is as follows:

[0042] Cutting the laminated chip inductor to be cut along the cutting line to obtain a single green billet;

[0043] The single green compact is subjected to a heating treatment to obtain an independent single green compact;

[0044] The independent single green compact is subjected to binder removal and sintering to obtain a single sintered body.

[0045] Specifically, the single green sheets are neatly arranged on the PET film tape, and a starch layer is adhered between the green sheet layer and the PET film; after the single green sheets are heated, the PET layer is naturally separated from the lower layer to obtain independent single green sheets without adhesion.

[0046] In some embodiments, the heating treatment temperature is 100-150°C, for example, but not limited to 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, and the time is 10-30min, for example, but not limited to 10min, 15min, 20min, 25min, 30min.

[0047] In the present disclosure, under the above-mentioned heating treatment conditions, the foam glue on the PET layer can completely lose its viscosity, so that the PET layer and the lower layer of the starch layer are naturally separated, and a single green body including the starch layer is obtained, and there is no adhesion between the single green bodies.

[0048] In some embodiments, the debinding temperature is 200-500°C, for example, but not limited to 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, and the time is 10-72h, for example, but not limited to 10h, 20h, 30h, 40h, 50h, 60h, 72h.

[0049] In some embodiments, the sintering temperature is 800-1000°C, for example, but not limited to 800°C, 850°C, 900°C, 950°C, 1000°C, and the sintering time is 4-24h, for example, but not limited to 4h, 8h, 12h, 16h, 20h, 24h.

[0050] In the present disclosure, under the above-mentioned debinding and sintering conditions, the starch layer is gradually and completely decomposed as the temperature rises, and will not enter the internal structure of the green layer to affect the quality or performance of the product, and a sintered body with good density can be obtained.

[0051] Compared with the prior art, the present invention has the following beneficial effects: by adding a starch layer between the green body layer and the PET layer, the green body layer has a buffering effect during the cutting process but does not affect the cutting accuracy, and no adhesion occurs after cutting, and the appearance and separability of a single green body are good. The starch layer can be gradually decomposed completely as the sintering process proceeds. Compared with the traditional powdering and anti-sticking method, on the one hand, the uniformity of starch distribution is improved, the material utilization rate is higher, and the anti-sticking effect is better. On the other hand, the starch layer located outside the green body gradually decomposes completely as the temperature rises, and will not enter the internal structure of the green body to affect the product quality or performance. A single sintered body with good density can still be obtained, and a miniaturized laminated inductor with high appearance qualification rate, strong reliability and high inductance can be prepared without changing the green body formula. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The present invention is a process flow chart for preparing a single sintered body of the multilayer chip inductor. DETAILED DESCRIPTION

[0053] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0054] As used herein:

[0055] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0056] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0057] When amount, concentration or other value or parameter is represented by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1-5", described range should be interpreted as including range "1-4", "1-3", "1-2", "1-2 and 4-5", "1-3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0058] In these examples, parts and percentages are by mass unless otherwise indicated.

[0059] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0060] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0061] In order to further illustrate the present invention, the pieces to be cut and the sintered body of the multilayer chip inductor provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0062] Example 1

[0063] like Figure 1 As shown, the present invention provides a method for preparing a single sintered body of a multilayer chip inductor, comprising the following steps:

[0064] S1: prepare the upper slurry and the lower slurry of the starch layer according to the mass percentage in Table 1;

[0065] The lower layer slurry is cast and dried on a PET film tape containing foam glue to obtain a lower layer in the starch layer; the upper layer slurry is further cast and dried on the lower layer to obtain an upper layer to obtain a starch layer; wherein the specific values ​​of the thickness of the upper layer, the thickness of the lower layer and the thickness of the starch layer are shown in Table 2;

[0066] S2: placing the green layer obtained by pressing on the starch layer obtained in step S1, so that the green layer contacts the upper layer, and a piece to be cut is obtained; wherein the thickness and thickness ratio of the starch layer and the green layer are as shown in Table 2;

[0067] S3: placing the piece to be cut obtained in step S2 on a cutting substrate, and cutting it with a cutting knife according to the position of the cutting line to obtain a single green piece;

[0068] S4: heating the single green pellet obtained in step S3 at 130° C. for 20 min, so that the foam glue on the PET film strip completely loses its stickiness, and the PET film strip and the starch layer are naturally separated to obtain an independent single green pellet;

[0069] S5: debinding the independent single green body obtained in step S4 at a temperature of 500° C. for 36 hours, and then sintering at a temperature of 900° C. for 16 hours to obtain a single sintered body;

[0070] The starch in Table 1 is corn starch with an average particle size of 14 μm, the binder is polyvinyl butyral, and the plasticizer is dioctyl phthalate; the thickness of the starch layer in Table 2 refers to the sum of the thickness of the upper layer and the thickness of the lower layer.

[0071] Table 1

[0072]

[0073]

[0074] Table 2

[0075]

[0076] Comparative Example 4

[0077] This comparative example provides a method for preparing a single sintered body of a multilayer chip inductor, comprising the following steps:

[0078] S1: Sprinkle corn starch particles with an average particle size of 14 μm evenly on a PET film tape containing foam glue;

[0079] S2: placing the green layer with a thickness of 370 μm prepared by pressing on the starch in step S1 to obtain a piece to be cut;

[0080] S3: placing the piece to be cut obtained in step S2 on a cutting substrate, and cutting it with a cutting knife according to the position of the cutting line to obtain a single green piece;

[0081] S4: heating the single green pellet obtained in step S3 at 130° C. for 20 min, until the foam glue on the PET film strip completely loses its stickiness, thereby obtaining an independent single green pellet;

[0082] S5: Debinding the independent single green body obtained in step S4 at a temperature of 500° C. for 36 hours, and then sintering at a temperature of 900° C. for 16 hours to obtain a single sintered body.

[0083] Performance Testing

[0084] The performance of the products obtained at various stages after the workpiece is cut is tested. The performance and test methods are as follows:

[0085] (1) Appearance qualification rate: A six-sided appearance machine is used to identify and judge the appearance of a single green pellet. The pellets without appearance defects such as deformation and local depression are qualified. The appearance qualification rate of 1,000 pellets in the same batch is calculated; the appearance qualification rate ≥ 95% is the qualified standard;

[0086] (2) Single-bead adhesion rate: Use a sieve to screen the independent single green billets, where the size of the sieve is greater than 20% of the height of the independent single green billets. After screening, the adhered products are on the sieve, and the non-adhered products are under the sieve. Measure the mass of the adhered products on the sieve and calculate the ratio to the total mass of 500,000 billets in the same batch. The single-bead adhesion rate ≤ 1% is considered acceptable;

[0087] (3) Sintering adhesion rate: Use a sieve to screen a single sintered body, where the size of the sieve is greater than 20% of the height of the single sintered body. After screening, the adhered products are on the sieve, and the non-adhesive products are under the sieve. Measure the mass of the adhered products on the sieve and calculate the ratio to the total mass of 500,000 pieces of the same batch. The sintering adhesion rate ≤ 0.5% is the qualified standard;

[0088] (4) Density: Use a scanning electron microscope (SEM) to photograph the surface and cross-section of a single sintered body to observe the porosity and grain growth of the surface and cross-section of the single sintered body. If there are no bubbles or pores and the grain growth is normal, it is qualified.

[0089] The test results are shown in Table 3.

[0090] Table 3

[0091]

[0092]

[0093] From the test results data in Table 3, it can be seen that the appearance qualification rate of the parts to be cut containing a starch layer of the present invention is more than 95.4%, the single-grain adhesion rate is below 1%, and the sintering adhesion rate is below 0.19%. This indicates that the starch layer of the parts to be cut in the present invention can improve the appearance qualification rate of the single green body after cutting and reduce the adhesion rate of the single green body and the single sintered body.

[0094] By comparing Example 1 with Examples 4-8, it can be seen that when the components and content relationship between the upper and lower layers in the starch layer and the relationship between the polarity of the solvent are met, the appearance qualification rate of a single green body reaches more than 98.5%, the single adhesion rate is below 0.31%, and the sintering adhesion rate is below 0.04%. Within the above preferred range, the appearance qualification rate of a single green body can be further improved, and the adhesion rate of a single green body and a single sintered body can be further reduced.

[0095] By comparing Example 5 with Examples 9-12, it can be seen that when the total thickness of the starch layer is 40-80 μm and the thickness ratio of the upper layer to the lower layer is 0.7-0.9, the appearance qualification rate of a single green body reaches more than 98.9%, the single adhesion rate is below 0.22%, and the sintering adhesion rate is below 0.06%. Within the above preferred range, the appearance qualification rate of a single green body can be further improved, and the adhesion rate of a single green body and a single sintered body can be further reduced.

[0096] By comparing Example 1 and Comparative Examples 1-2, it can be seen that Comparative Example 1 contains only a single starch layer, and the starch content in the starch layer is low and the binder content is high (compared with the middle and upper layers of the starch layer in Example 1), and the adhesion rate and sintering adhesion rate of the single green body are both unqualified; Comparative Example 1 contains only a single starch layer, and the starch content in the starch layer is high and there is no binder (compared with the middle and upper layers of the starch layer in Example 1), and the appearance qualification rate and density of the single green body are both unqualified; It means that only a single starch layer is used and the quality of starch and binder is not within the scope of the present invention, and it is impossible to achieve the simultaneous improvement of the appearance qualification rate of the single green body, the adhesion rate of the single green body and the single sintered body, and the sintering density performance.

[0097] By comparing Example 5 and Comparative Example 3, it can be seen that in Comparative Example 3, the content of starch in the upper layer is less than that in the lower layer, and the content of binder in the upper layer is greater than that in the lower layer. The appearance qualification rate of the single green billet is unqualified, indicating that the quality of starch and binder in the upper and lower layers of the starch layer is not within the scope of the present invention, which will lead to a decrease in the appearance qualification rate of the single green billet.

[0098] By comparing Example 5 and Comparative Example 4, it can be seen that Comparative Example 4 is a prior art of sprinkling starch granules on a PET film to prevent adhesion. It can be seen that the appearance qualification rate, single-grain adhesion rate, sintering adhesion rate and density of the single green body obtained in Comparative Example 4 are all unqualified, indicating that the present invention adds a starch layer between the PET layer and the green body layer, which can effectively increase the appearance qualification rate of the single green body, ensure good density, and reduce the adhesion rate of the single green body and the single sintered body.

[0099] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A piece to be cut of a laminated chip inductor, characterized in that: It includes a PET layer, a starch layer and a green layer in order from bottom to top, wherein the starch layer includes an upper layer and a lower layer, the lower layer is in contact with the PET layer, and the upper layer is in contact with the green layer; The components of the starch layer include starch, a binder and an organic solvent, wherein, based on the mass of the starch layer as a whole, the mass of the starch in the upper layer is greater than the mass of the starch in the lower layer, and the mass of the binder in the upper layer is less than the mass of the binder in the lower layer.

2. The piece to be cut of the multilayer chip inductor according to claim 1, characterized in that: The polarity of the organic solvent in the upper layer is greater than the polarity of the organic solvent in the lower layer.

3. The piece to be cut of the multilayer chip inductor according to claim 2, characterized in that: The organic solvent in the upper layer is at least one of ethanol, ethyl acetate, propyl acetate, toluene, and butanone; the organic solvent in the lower layer is at least one of toluene, xylene, propanol, isobutanol, and n-butanol.

4. The piece to be cut of the multilayer chip inductor according to claim 1, characterized in that: Taking 100 parts by weight of the lower layer slurry for preparing the lower layer, the lower layer slurry comprises the following components in parts by weight: 20-45 parts by weight of starch, 5-12 parts by weight of a binder, 49-64 parts by weight of an organic solvent, and the remainder being a plasticizer; Taking 100 parts by weight of the upper slurry for preparing the upper layer, the upper slurry includes the following components in parts by weight: 25-55 parts by weight of starch, 4-7 parts by weight of a binder, 38-67 parts by weight of an organic solvent, and the remainder being a plasticizer.

5. The piece to be cut of the multilayer chip inductor according to claim 1, characterized in that: The starch is at least one of corn starch, potato starch and sweet potato starch; And / or, the binder is at least one of polyvinyl butyral, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, acrylic resin, and hydroxyethyl cellulose; And / or, the plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, di(di-ethylhexyl) adipate, di(di-ethylhexyl) sebacate, tricresyl phosphate, epoxidized soybean oil, and tributyl citrate.

6. The piece to be cut of the multilayer chip inductor according to claim 1, characterized in that: The thickness of the starch layer is 30-100 μm, and the thickness ratio of the upper layer to the lower layer is 0.6-1.

7. The piece to be cut of the multilayer chip inductor according to claim 1, characterized in that: The thickness ratio of the green layer to the starch layer is 3.5-15.

8. A method for preparing a piece to be cut of a multilayer chip inductor as claimed in claims 1 to 7, characterized in that: The following steps are involved: Preparing an upper slurry and a lower slurry of the starch layer; Casting the lower layer slurry on the PET layer to obtain the lower layer, and further casting the upper layer slurry on the lower layer to obtain the upper layer, thereby obtaining the starch layer; The green sheet layer is placed on the starch layer to obtain pieces to be cut of the laminated chip inductor.

9. A single sintered body of a multilayer chip inductor, characterized in that: The to-be-cut pieces of the multilayer chip inductor as claimed in claims 1 to 7 are sequentially cut, heated and debinded and sintered to obtain a single sintered body of the multilayer chip inductor.

10. The single sintered body of the multilayer chip inductor according to claim 9, characterized in that: The heating treatment temperature is 100-150°C and the time is 10-30min; And / or, the debinding temperature is 200-500°C and the time is 10-72h; And / or, the sintering temperature is 800-1000° C. and the sintering time is 4-24 hours.